The Social Communication Competence as a Soft Skill of the School Leadership in Archipelago Region - Ismail, Khodijah Ismail; Sutarman,; Tumin,; Yudhakusuma, Dudi; Mayasari, Linda Ika (International Journal of Psychosocial Rehabilitation, 2020)
Education is an important part of development in coastal areas and border islands because it has specific demographic and geographic characteristics. Therefore a leadership style that is able to understand this specific situation is needed. This study aims to examine the application of principals' social communication skills in situational leadership styles to improve teacher / student interaction and ultimately improve teacher performance and the learning process of madrasah schools in the coastal areas of the border island. This research was conducted at MAN Tanjungpinang, Riau Islands. Data collection using questionnaires and interviews with 28 teachers, with a quantitative approach. The results showed that there was a positive relationship between the principal's situational leadership style and teacher performance (significant value (P-value) of 0.049